Transcriptome Analysis of the Anti-TGFβ Effect of Schisandra chinensis Fruit Extract and Schisandrin B in A7r5 Vascular Smooth Muscle Cells - Sanghoon Lee; Jung Nyeo Chun; Hae-Jeung Lee; Hyun Ho Park; Insuk So; Ju-Hong Jeon; Eun-Jung Park (Life, 2021)
Schisandra chinensis fruit extract (SCE) has been used as a traditional medicine for treating vascular diseases. However, little is known about how SCE and schisandrin B (SchB) affect transcriptional output-a crucial factor for shaping the fibrotic responses of the transforming growth factor β (TGFβ) signaling pathways in in vascular smooth muscle cells (VSMC). In this study, to assess the pharmacological effect of SCE and SchB on TGFβ-induced transcriptional output, we performed DNA microarray experiments in A7r5 VSMCs. We found that TGFβ induced distinctive changes in the gene expression profile and that these changes were considerably reversed by SCE and SchB. Gene Set Enrichment Analysis (GSEA) with Hallmark signature suggested that SCE or SchB inhibits a range of fibrosis-associated biological processes, including inflammation, cell proliferation and migration. With our VSMC-specific transcriptional interactome network, master regulator analysis identified crucial transcription factors that regulate the expression of SCE- and SchB-effective genes (i.e., TGFβ-reactive genes whose expression are reversed by SCE and SchB). Our results provide novel perspective and insight into understanding the pharmacological action of SCE and SchB at the transcriptome level and will support further investigations to develop multitargeted strategies for the treatment of vascular fibrosis.